MENINGKATKAN EFEKTIVITAS PENGAJARAN AL-QUR'AN DALAM KURIKULUM PENDIDIKAN ISLAM - Fathurahman Fathra (Atthiflah: Journal of Early Childhood Islamic Education, 2023)
This study aims to increase the effectiveness of teaching the Qur'an in the Islamic education curriculum. Through qualitative research methods with a case study approach, data were obtained through class observations, interviews, and document analysis. The results showed that factors such as the teacher's understanding and experience in teaching the Qur'an, effective pedagogical skills, and the integration of Islamic values influence teaching effectiveness. Applying appropriate teaching strategies, such as interactive methods, relevant support resources, and training programs for teachers, can increase the effectiveness of teaching the Qur'an. Integration of Islamic values in teaching is also important to help students understand and internalize the teachings of the Qur'an in everyday life. Involve parents and the community in the process of teaching the Qur'an for a holistic approach to Islamic education. The conclusion of this study is that improving the effectiveness of teaching the Qur'an requires collaboration between teachers, educational institutions, parents, and the community. Training programs are needed to improve teacher understanding and skills, as well as the development of relevant support resources. The integration of Islamic values must be the main focus in increasing the effectiveness of teaching. Implementation of appropriate teaching strategies is expected to provide benefits for students in understanding and practicing the teachings of the Qur'an.